The War Theme in the European Literature - Shawon, Sahariar Alam (International Journal of Language and Literary Studies, 2024)
This research paper investigates the profound impact of war on European literary traditions, focusing on key events for example World War I, World War II, and the Spanish Civil War. Through a qualitative analysis of sensational novels and poems, the paper explores the representation of war’s brutality, trauma, and societal effusions. The study portrait into All Quiet on the Western Front by Erich Maria Remarque, In Flanders Fields by John McCrae, and The Waste Land by T.S. Eliot discusses the portrayal of World War One. For World War Two, works such as The Diary of a Young Girl by Anne Frank and Do Not Go Gentle into That Good Night by Dylan Thomas are analyzed, while For Whom the Bell Tolls by Ernest Hemingway is explored within the context of the Spanish Civil War. These works explore key themes such as disillusionment, loss, resilience, and patriotism, and critically examining of political and social structures. The paper emphasizes how literature serves as a mirror for the emotional and psychological toll war takes on both individuals and society, shaping our collective memory of war's aftermath. The study concludes that war literature not only captures the human experience during conflict but also provides enduring perspectives on the wider social and political changes that war brings.